2022
DOI: 10.1089/ast.2021.0144
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Thermal, and Radiation Resistance of an Iron Porphyrin: A Model Study of Biosignature Stability

Abstract: Metal complexes of porphyrins and porphyrin-type compounds are ubiquitous in all three domains of life, with hemes and chlorophylls being the best-known examples. Their diagenetic transformation products are found as geoporphyrins, in which the characteristic porphyrin core structure is retained and which can be up to 1.1 billion years old. Because of this, and their relative ease of detection, metalloporphyrins appear attractive as chemical biosignatures in the search for extraterrestrial life. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…(2) Haemin showed well-defined decomposition behaviour between ∼240 and 260°C where two processes occurred, namely decarboxylation and formation of HCl. The iron porphyrin core, which may serve as an important biosignature (Pleyer et al, 2022), remained intact at 260°C. However, it decomposed at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Haemin showed well-defined decomposition behaviour between ∼240 and 260°C where two processes occurred, namely decarboxylation and formation of HCl. The iron porphyrin core, which may serve as an important biosignature (Pleyer et al, 2022), remained intact at 260°C. However, it decomposed at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…1(a). Iron porphyrins such as haemin are attractive biosignatures in the search for extraterrestrial life (Pleyer et al, 2022). In crystals of haemin the molecules are linked pairwise by hydrogen bonds between propionic acid side chains (-CH 2 CH 2 COOH) (Koenig, 1965;Kaduk et al, 2016).…”
Section: Haeminmentioning
confidence: 99%
“…The formation of a metalloporphyrin complex with a metal cation further stabilizes the macrocyclic structure against geochemical degradation [33,43,44]. Heme and heme-like porphyrins have been described as resistant to changes in environmental pH and remain relatively unchanged at both low (e.g., pH = 0) and high pH (e.g., pH = 13.5) [180]. These molecules have also demonstrated resistance to degradation by high temperatures (330 • C) [180][181][182].…”
Section: The Preservation Potential Of Heme-based Proteinsmentioning
confidence: 99%
“…Although there are several reports on the potentially prebiotic synthesis of porphyrins, porphyrins are considered as biomarkers (“biosignatures”), , i.e., if detected on other planets than the Earth in the solar system or on extrasolar planets would be taken as sign of extraterrestrial life forms. If porphyrins formed on the early Earth, before life originated, metalation of the porphyrins would probably have happened relatively easily, , i.e., iron porphyrins similar to heme b would have formed due to the large abundance of iron ions on the prebiotic Earth.…”
Section: Prebiological Considerationsmentioning
confidence: 99%
“…Although probably not abundant in the early atmosphere, H 2 O 2 and O 2 might have been formed on the surface of the early Earth, 149 arguing that not only the chemical composition of the atmosphere should be considered but also the likely heterogeneous distribution of chemical compounds on the Earth's surface. 144 Various studies have shown that H 2 O 2 easily forms from H 2 O on the surface of minerals, for example, pyrite (FeS 2 ) 150,151 or silicates (SiO 2 ), 152 or on the surface of micrometer-sized water Although there are several reports on the potentially prebiotic synthesis of porphyrins, 154−156 porphyrins are considered as biomarkers ("biosignatures"), 157,158 i.e., if detected on other planets than the Earth in the solar system or on extrasolar planets would be taken as sign of extraterrestrial life forms. If porphyrins formed on the early Earth, before life originated, metalation of the porphyrins would probably have happened relatively easily, 159,160 i.e., iron porphyrins similar to heme b would have formed due to the large abundance of iron ions on the prebiotic Earth.…”
Section: Prebiological Considerationsmentioning
confidence: 99%